PENGEMBANGAN MODEL CONTEXTUAL TEACHING AND LEARNING DENGAN KOMPONEN MULTIMEDIA PADA MATA PELAJARAN PAI - Shofiyah, St. (Fakultas Tarbiyah, Universitas Ibrahimy, 2020)
The background of this research is processing of Islam religion Lesson’s learning with done by using the model training contextual teaching and learning that during this time had not been maximal. The purposes of this research are: first, to describe the application of model of training CTL with component multimedia at Islam Religion lesson’s educating in SMP Negeri 1 Banyuputih. Second, to describe the design of development model of training CTL with component multimedia at Islam Religion lesson’s educating in SMP Negeri 1 Banyuputih. Third, to describe the level of design applying in development model of training CTL with component multimedia at Islam Religion lesson’s educating in SMP Negeri 1 Banyuputih. Fouth, to describe the effect of applying development model of training CTL with component multimedia at Islam Religion lesson’s educating in SMP Negeri 1 Banyuputih. Generally the time of this research are research and development which are done by four step. Study preface, planning, first product development, evaluation.